Efektivitas Kegiatan Penyuluhan Pendidikan Politik Pemilih Pemula di Badan Kesatuan Bangsa dan Politik Kabupaten Musi Banyuasin - Nurfitriana, Nurfitriana; Yusuf, Muhammad; Berlian, Ong (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2021)
This study aims to analyze the effectiveness of Political Education Counseling for First-Time Voters Program in National Unity and Politics Agency of Musi Banyuasin Regency. This is a qualitative research. Data and information were collected through interviews. This studyshows that the Political Education Counseling for First-Time Voters Program in National Unity and Politics Agency of Musi Banyuasin Regency has been implemented optimally. Political Education Counseling Program for First-Time Voters aim to spread information regarding steps, timeline, and election program; to increase people’s knowledge, understanding, and awareness on their rights and obligations in election; and to increase voters’ participation in an election. However, budget or funds are currently deemed insufficient due to the sizeable area of Musi Banyuasin Regency and the distance between the districts within it. Therefor, it can be concluded that: a) It is necessary to improve the cooperation with related parties to conduct counseling for first-time voters in Musi Banyuasin Regency, and b) The implementation of political education counseling for first-time voters in Musi Banyuasin Regency must be carried out continuously and the number of human resources involved in this program must be increased.